SAT0527 Rituximab prescription patterns and efficacy in the induction treatment of anca-associated vasculitis in a belgian multicentric cohort. (12th June 2018) - Vandergheynst, F.; Chasseur, P.; Nicolas, J.-B.; von Frenckell, C.; Blockmans, D.
Abstract : Background: The RAVE trial has revolutionised the induction treatment of ANCA-Associated Vasculitis (AAV, including GPA, granulomatosis with polyangiitis and MPA, microscopic polyangiitis), by demonstrating non-inferiority of rituximab compared with cyclophosphamide 1 . Objectives: To study AAV patients' characteristics, rituximab prescription practices and efficacy in AAV induction treatment in 4 Belgian university hospitals. The patient population, selected according to the Belgian reimbursement criteria, is relatively homogeneous and comparable to the one of RAVE trial. Methods: 57 patients, receiving rituximab as AAV induction therapy since May 2014, were enrolled in an observational retrospective multicenter trial involving 4 Belgian university hospitals. We have focused on the type of AAV (GPA/MPA), ANCA specificity (anti-PR3/MPO), prescriber's speciality, used reimbursement criteria, organ involvements, severity of the flares (according to BVAS-WG definition) and finally rituximab efficacy in AAV induction treatment by considering the RAVE primary (complete remission without prednisone) and secondary (complete remission with prednisone <10 mg, rates of relapses) outcomes at 6, 12, 18 and 24 months. Results: The most frequent subtype of AAV was GPA (84%). The main indication was relapsing disease (54.4%), followed by contra-indication to cyclophosphamide (38.6%). 66.7% of the patients reached complete remission with prednisone <10 mg at 6 months, and 55.3% at 12 months, 40% at 18 months, 25% at 24 months respectively. In the "severe disease" subgroup, 73% reached complete remission with prednisone <10 mg at 6 months, 58.8% at 12 months, 50% at 18 months and 32% at 24 months. The rates of complete remission without steroids were very low at 6, 12, 18 and 24 months (between 0%–6%) but our patients were not asked to follow a glucocorticoid tapering scheduled for complete withdrawal of prednisone after 6 months and were usually maintained under low-dose prednisone. Relapse rates were high between 18 and 24 months both in the total group and in the severe disease subgroup (due to the fact that rituximab is not reimbursed for maintenance treatment in Belgium). The subtype of ANCA was not predictive of the risk of relapse. Conclusions: Our results confirm – in a "real-life" cohort of patients selected according data of RAVE trial – those of RAVE regarding complete remission rates at 6 months with prednisone 10 mg/j. The high prevalence of relapses – in particular after 18 months – underlines the need to optimise maintenance treatment after an induction treatment with rituximab. Reference: [1] Specks U, Merkel PA, Seo P, et al. Efficacy of remission-induction regimens for ANCA-associated vasculitis. N Engl J Med2013:369(5):417–27. Disclosure of Interest: None declared